GEOSYSTEMIC APPROACH OF GEORGES BERTRAND: A PERSPECITVE ON GEOGRAPHICAL THINKING - Ferreira, Matheus de Oliveira (2023)
Epistemological studies in the field of Physical Geography have been occurring more frequently in recent years but still less significantly than the proposals associated with Human Geography. In this context, even given the relevance of geosystemic research to the national debate, little has been thought of the genesis and structuring of such knowledge - though the debate has been given new impetus by new publications in recent years -highlighting the knowledge and trajectory of essential researchers for the development of the society-nature integrator ideology in Geography. Therefore, this paper aims to discuss and periodise Georges Bertrand's geographical thinking, one of the most renowned researchers on geosystem and landscape. With interpretive lens, we analyse how this author had worked on the geosystem, in order to draw up interpretative guidelines for understanding the French biased geosystemic approach in which the mentioned author is one of the major references. As a methodological procedure, the study periodised the author & PRIME;s work in two distinct chronological moments on the basis of its theoretical, methodological and epistemic foundations. The study has concluded that Bertrand's geosystemic production for the years under review is in a constant renewal movement as the geosystem and landscape concept has been further rethought tied to transformations in the relationship between society and nature.